SURGICAL REMOVAL OF A PERFORATING INTESTINAL FOREIGN BODY IN A BEAGLE PUP – A CASE REPORT - Ramankutty, Soumya; Lekshmi , S.L; K.D , John Martin (International Journal of Allied Sciences (IJAS), 2022)
Gastrointestinal foreign bodies in small companion animals are a common condition requiring prompt diagnosis and surgical intervention. This case report describes the successful surgical removal of a perforating intestinal foreign body in a 35-day-old Beagle pup. The pup presented with symptoms of distended abdomen, blood tinged diarrhea, and respiratory distress with a history of pain on palpation. Radiographic examination revealed the presence of a radiopaque foreign body in the ileocaecocolic junction, which was tentatively diagnosed as a penetrating intestinal foreign body. An emergency exploratory laparotomy was performed, and a stapler pin was retrieved from the ileocaecocolic junction by enterotomy. The animal received intravenous fluids, antibiotics, H2 antagonists, and vitamin B supplements postoperatively for five days and had an uneventful recovery. The prompt diagnosis and surgical intervention led to the complete recovery of the Beagle pup.